Western monasticism ante litteram the space of monastic observance in late antiquity and the early Middle Ages. - Dey, Hendrik W. 1976-; Fentress, Elizabeth (Turnhout Brepols, 2011)
"Space has always played a crucial part in defining the place that monks and nuns occupy in the world. Even during the first centuries of the monastic phenomenon, when the possible varieties of monastic practice were nearly infinite, there was a common thread in the need to differentiate the monk from the rest: whatever else they were supposed to be, monks were beings apart, unique, in some sense separate from the mainstream. The physical contours of monastic topographies, natural and constructed, are thus fundamental to an understanding of how early monks went about defining the parameters of their everyday lives, their modes of religious observance, and their interactions with the larger world around them. The group of eminent historians and archaeologists present at the American Academy in Rome in March, 2007 for the conference 'Western monasticism ante litteram'"--Back cover.
Keywords: Monasteries -- Europe -- History -- To 1500 -- Congresses; Monasticism and religious orders -- History -- Early church, ca. 30-600 -- Congresses; Monasticism and religious orders -- History -- Middle Ages, 600-1500 -- Congresses; 271 "00/06" -- Kloosterwezen. Religieuze orden en congregaties. Monachisme--?"00/06"; 271.05 -- Ontstaan van het monnikenwezen. Oudste monachisme